IMPROVING GROWTH OF PATCHOULI CUTTINGS USING PLANT GROWTH REGULATORS AND GROWING MEDIA - Nur Auliatul Qumaini Nasrah; Muhidin; Syamsu Alam (RADJA PUBLIKA, 2025)
Patchouli plant (Pogostemon cablin Benth.) is one of the essential oil producing plants which is widely used in the pharmaceutical, cosmetic and perfume fields, especially as a mixture or fixative (fragrance binder). The productivity and success rate of the initial growth of patchouli plants are largely determined by the cultivation techniques used. The cuttings used are stem cuttings with the best number of 4 nodes and have 2 remaining leaves for photosynthesis. The purpose of this study was to analyze the effect of growth regulator treatment and planting media composition on the growth of patchouli cuttings. The study used a factorial randomized block design with 2 factors, namely the first factor of planting media (M) consisting of 2 levels, namely: M0 = Ultisol soil (control); M1 = Ultisol soil + coconut shell biochar (2:1). The second factor of PGR (N) consists of 4 levels, namely: N0 = Water (control); N1 = 100% coconut water; N2 = 45% shallot extract; N3 = Rootone-F 150 ppm. The results showed that each independent treatment had a very significant effect on the variables of fresh cutting weight (g), root volume (cm3) and root morphology. Furthermore, the interaction of planting media and PGR treatments had a very significant effect on the variables of fresh cutting weight, root volume and root morphology. Ultisol soil + coconut shell biochar (2:1) and Rootone-F 150 ppm planting media were the best treatments to increase the growth of patchouli cuttings.